Rhythmic elements: a motivating strategy to teach english vocabulary - Argudo Serrano, Juanita Catalina
The present research consists of a research that looks for finding the way in which the use of rhythmic elements in an English class of 30 five-year-old boys can help to motivate these children as well as enhance their vocabulary acquisition. There are various theories which backup this project; such theories explain the way in which people learn languages. It was necessary to consider some theories and approaches for language acquisition, and some helpful theories of vocabulary acquisition to be used by language teachers. It is also important to mention some teaching and learning strategies which are used not only by the teacher but also by the students, who are the main participants in the teaching and learning process. It is important to reflect on the use of rhyme and rhythm to help students learn not only meaning but also pronunciation, and store it in their minds , this way they know, at any moment, which words they need to convey a message. Considering all the above ideas, the contents and the instruments to be taught were chosen and applied in this English class. After a period of 3 months of application of this strategy, the results show that children felt comfortable and enjoyed working with rhythmic elements. The results also show that there is a considerable improvement in vocabulary knowledge if the pre- and post-tests are compared. In conclusion, it is possible to say that rhythmic elements motivate children to learn a foreign language as well as help them improve their vocabulary knowledge.